Роль информационных сайтов в обеспечении данными общества - Иванинская, И.И. (Культура народов Причерноморья, 2013)
Материалы данной статьи содержат, в основном, ознакомительный характер. Статья
посвящена рассмотрению видов сайтов, а также описанию самых востребованных из них.
Характеристика необходимости и распространения информационных сайтов в настоящее время. В
статье даётся определение понятия "сайт", а также рассмотрены виды сайтов. Каждому виду
сайтов даётся определение: промо-сайт; корпоративный сайт; портал, информационный сайт. В
статье делается упор именно на информационных сайтах. В работе описано ежегодное исследование
компании "Netcraft"о развитии сайтов в интернете. Матеріали даної статті містять, в основному, ознайомчий характер. Стаття присвячена
розгляду видів сайтів, а також опису найбільш затребуваних з них. Характеристика необхідності і
розповсюдження інформаційних сайтів в даний час. У статті дається визначення поняття "сайт", а
також розглянуто види сайтів. Кожному виду сайтів дається визначення: промо-сайт; корпоративний
сайт; портал, інформаційний сайт. У статті робиться упор саме на інформаційних сайтах. У роботі
описано щорічне дослідження компанії "Netcraft" про розвиток сайтів в інтернеті. In general materials of the article contain acquainting character. The article is devoted to
consideration of site types and also description of the most popular ones. Description of necessity and
distribution of informative sites at present. There is definition to concept "site" is given in the article, and also
types of sites are considered. Each type of sites is defined: promo-site; corporate site; portal, information site. In
the article on the information sites is placed emphasis. In the work annual research of "Netcraft" company about
development of sites in the Internet is described. According to research of 2011 – there are more than 270
million functioning sites in the Internet. In December, 2012 the firm published next report which testified that
today there are 633 706 564 registered portals in the Internet. And this number constantly grows every day.
Information sites are necessary now in all spheres of activity. Now there are no person who never in life use
Internet resources. Information sites are necessary for tourists, students, housewives, and for everyone who
wants to learn something new. The informative sites are the most visited ones because they are updated rather
often and provide information much wider.